Pentingnya Etika Keilmuan bagi Pengembangan Profesionalisme Guru PAUD dalam Pembelajaran Anak Usia Dini - Rahmatin, Luluk Arifatur; Aisyah, Eny Nur (Journal of Childhood Education, Development and Parenting, 2024)
This study aims to examine the importance of scientific ethics in the development of professionalism of Early Childhood Education (PAUD) teachers in early childhood learning. Scientific ethics that include basic principles such as honesty, objectivity, integrity, and openness play a very important role in improving the quality of teaching and teacher interaction with children. In the context of early childhood education, the application of scientific ethics by teachers not only helps improve the quality of education, but also forms positive character and attitudes in children. Through a qualitative approach, this study analyzes how the application of scientific ethics in the context of education can support PAUD teachers to become more professional. This study also emphasizes the importance of training for PAUD teachers to strengthen scientific ethics in their educational practices. Scientific ethics that are consistently applied by PAUD teachers can improve their pedagogical skills and have a positive influence on the development of students. The results of the study indicate that the application of scientific ethics helps PAUD teachers in improving pedagogical competence, building better relationships with students, and creating a more effective and supportive learning environment. In addition, this study underlines the importance of cooperation between educational institutions, government, and the community in supporting the implementation of scientific ethics in the school environment. Recommendations provided include improving scientific ethics training programs, as well as strengthening regulations and policies that support the professionalism of PAUD teachers. Thus, it is hoped that PAUD teachers can carry out their roles better and make a positive contribution to the development of early childhood